Renal dysfunction is an independent risk factor for bleeding after gastric ESD - Yoshioka, Teppei; Nishida, Tsutomu; Tsujii, Masahiko; Kato, Motohiko; Hayashi, Yoshito; Komori, Masato; Yoshihara, Harumasa; Nakamura, Takeshi; Egawa, Satoshi; Yoshio, Toshiyuki; Yamada, Takuya; Yabuta, Takamasa; Yamamoto, Katsumi; Kinoshita, Kazuo; Kawai, Naoki; Ogiyama, Hideharu; Nishihara, Akihiro; Michida, Tomoki; Iijima, Hideki; Shintani, Ayumi; Takehara, Tetsuo (Endoscopy International Open, 2015)
Background and study aims: The number of patients with chronic kidney disease (CKD) is increasing worldwide and gastric cancer sometimes occurs with CKD. However, the safety and feasibility of endoscopic submucosal dissection (ESD) for patients with CKD are not clear. The aim of this study is to clarify the feasibility and safety of gastric ESD for patients with CKD. Patients and methods: This was a multicenter retrospective cohort study. In total, 144 patients with CKD who underwent gastric ESD between May 2003 and October 2012 were enrolled. The patients were divided into three groups: stage 3 (estimated glomerular filtration rate [eGFR]: 30 – 59 mL/min), stage 4 (eGFR: 15 – 29 mL/min), and stage 5 (eGFR: < 15 mL/min) according to the Kidney Disease Improving Global Outcomes Guidelines. The en bloc and curative resection rates and complications were assessed as short-term outcomes. Overall survival was analyzed using Kaplan – Meier methods.Results: In total, 92 patients were in stage 3 CKD; 23 in stage 4; and 29 in stage 5, including 19 patients in hemodialysis. The en bloc resection rate was 95.8 %. Post-ESD bleeding was observed in four patients with stage 5 CKD (13.8 %), three with stage 4 (13.0 %), and one with stage 3 (1.1 %). All bleeding could be controlled by endoscopic hemostasis, but five patients required blood transfusion. Perforation occurred in two patients (6.9 %) with stage 5 CKD, none (0 %) with stage 4, and two (4.3 %) with stage 3. Multivariate Poisson regression analysis revealed CKD stage 4 was a critical factor related to bleeding, whereas diabetes mellitus and CKD stage 5, which largely consist of patients receiving hemodialysis, were not. The median observation period of patients who achieved curative resection was 25.9 months (range 0.8—112.7 months) and the 3-year overall survival rate was 92.5 %. Conclusions: Estimated GFR is a significant independent predictive factor of post-ESD bleeding in patients with CKD.